Respuesta :

LC447

Answer:

a) 5  b) 1  c) 0  d) -4

Explanation:

a) 10[(1/2+1/4) + 2(1/8)] ÷ 2

Ok, there's a lot going on. You will want to follow PEMDAS, the acronym of the Order of Operations. It stands for Parentheses, Exponents, Multiplication/Division, and Addition/Subtraction. The M/D can be switched depending on what comes first from left to right, and same goes for A/S.

First, start off by doing everything in the brackets.

Let's add 1/2 and 1/4. To add fractions, they have to have a common denominator. I'm making 1/2 into 2/4 but multiplying the top and bottom by 2. Now it is 2/4 + 1/4 so we can add to get 3/4.

The other thing inside the brackets is 2(1/8). We can just multiply straight across and get 2/8. This can be simplified to 1/4.

Now, we add 3/4 and 1/4. The denominators are already the same, so we can just add them together to get 4/4 or 1.

Rewriting the equation, we now have 10(1)÷2

10•1 = 10

10 ÷ 2 = 5

The answer to question a is 5.

b) √(0.6)² + (0.8)²

First, we need to square both terms. Squaring is the same as multiplying the number by itself.

0.6 • 0.6 = 0.36

0.8 • 0.8 = 0.64

Add them together: 0.36 + 0.64 = 1

√1 = 1

The answer to question b is 1.

c) (1/5 - 3/5) • √6•3/2 + (√36 ÷ √5²)

Let's start with the first bit: (1/5 - 3/5)

The denominators are the same, so just subtract and you get -2/5

The second bit now: [tex]\sqrt{6 *\frac{3}{2} }[/tex]

Multiply across and you get 18/2, which can be simplified to 9

√9 = 3

The third section: ([tex]\sqrt{36}[/tex]÷ [tex]\sqrt{5^{2} }[/tex])

The square root of 36 = 6 (because 6•6=36, so it's right)

The square root and the square cancel each other out, so the second part is 5.

6 ÷ 5 = 1.2

Now put it all together: -2/5 • 3 + 1.2

I'm making the 1.2 into a fraction so it is the same as the fraction: 1.2 = 6/5

We now have -2/5 • 3 + 6/5

First we multiply -2/5 and 3 across:

-2/5 • 3 = -6/5

Now we add -6/5 and 6/5 across:

-6/5 + 6/5 = 0

d) [-1.5 + √0.25 - (-0.75)] • 2^4

Doing the brackets first:

The square root of 0.25 = 0.5 (because 0.5 • 0.5 = 0.25)

-1.5 + 0.5 - -0.75

-1 + 0.75 (subtracting a negative make a positive)

-0.25

-0.25 • 2^4

2^4 = 16 (this is saying 2•2•2•2 which is 16)

-.25 • 16 = -4